Caraterización citogenética del pez tropical de agua dulce Parachromis managuensis (Pisces: Cichlidae) - Arias-Rodriguez, Lenin (2006)
To describe the cytogenetics of the jaguar cichlid fish Parachromis managuensis, we collected eight males and 13 females in Villahermosa, Tabasco, México. The specimens were processed with standard cytogenetic techniques (slightly modified), and high quality fields of chromosomes in mitosis and meiosis were obtained; 14 of these fields were analyzed by meristics and statistics methods. The specimens presented a diploid modal number of 2n=48 chromosomes, which is similar to the number reported for others Central American cichlids; five pairs were submetacentric-metacentrics(biarmed) and 19 were subtelocentric-telocentric (uni-armed), giving a fundamental number (NF) of 58. The haploid number was confirmed by counting meiotic fields in metaphase I. There was not evidence of heteromorphism: sexual chromosomes were not identifiable.